Artemilavanolides A and B, two sesquiterpenoids with a 6-oxabicyclo[3.2.1]octane scaffold from Artemisia lavandulaefolia. Issue 21 (21st May 2020) - Ding, Lin-Fen; Peng, Li-Yan; Zhou, Hao-Feng; Song, Liu-Dong; Wu, Xing-De; Zhao, Qin-Shi
Graphical abstract: Highlights: Two unprecedented sesquiterpenoids were obtained from Artemisia lavandulaefolia . The structures of 1 and 2 possessed 6-oxabicyclo[3.2.1]octane scaffold. The absolute configurations of 1 and 2 were established by analysis of ECD data. Compound 1 exhibit moderate neurotrophic activity. Abstract: Artemilavanolides A (1 ) and B (2 ), two unprecedented sesquiterpenoids with 6-oxabicyclo[3.2.1]octane scaffold, as well as one known biogenetically related sesquiterpenoid, 11 β, 13-dihydrosantamarin (3 ), were isolated from the aerial parts of Artemisia lavandulaefolia . The structures and absolute configurations of 1 and 2 were characterized by analysis of HRESIMS, NMR spectroscopic, single crystal X-ray diffraction, and electronic circular dichroism (ECD) data. The plausible biogenetic pathway for 1 and 2 was also proposed. Compound 1 was found to enhance the neurite outgrowth of NGF-mediated PC12 cells at a concentration of 10 μM.